E-Module of Mathematics Economic Using Heutagogy Approach for Distance Learning: Is It Effective? - Sholikhah, Ni'matush; Pamungkas, Heni Purwa; Surjanti, Jun; Sakti, Norida Canda (Journal of Education Technology, 2022)
Heutagogy approach is the development of andragogy learning which focuses on students’ self-determined learning. This approach can be used as an alternative for distance learning. To support the learning process, an e-module based on heutagogy is needed. Therefore, the purpose of this study was to create and analyze the effectiveness of E-Module in Mathematics Economic based on the Heutagogy Approach in distance learning. Research design used 4-D model consists of define, design, develop, and desseminate stages. Examining the E-module effectiveness was using experiment research with one group pre-test-post-test design which involved 66 students of Economics Education as participants. Data collection are carried out with questionnaire and analyzed with several test, namely: Kolmogorov-Smirnov Normality Test, Wilcoxon signed-rank test.The results of this study revealed that: 1) E-module of mathematics economic using Heutagogy Approach feasible as learning media, 2) there is an effect of using E-module of Mathematics Economic using Heutagogy Approach for Distance Learning. E-module can increases students learning outcomes and helps them to study independently during distance learning. For future research, it is suggested to analyze another variabels, such as: students’ critical thinking skills and students’ logical- mathematical thinking ability.